Coyuntura Económica - María Carolina Rozo; Emma Beatriz Castro; Ángela Patricia Bedoya; Holmes Sánchez; Guillermo Aponte (Revista de Economía & Administración E-ISSN 2463-1035 ISSN 1794-7561, 2010)
Análisis económico